Pathways to Recovery and Desistance - Best, David (Policy Press, 2019)
Available Open Access under CC-BY-NC licence. Putting forward a new recovery roadmap and new reform models for prisoners reintegration, Best provides an accessible guide for the implementation of community partnerships for people in recovery from substance abuse or rehabilitating from offending. Using case studies and a strengths-based approach the book emphasizes the importance of long-term recovery and the role that communities and peers play in the process.